Glory and beauty in the world and in God a critique of Hans Urs von Balthasar - Brown, David 1948- (2018)
After briefly noting Geoffrey Rowell's interest in both themes, this article proceeds to examine Balthasar's equation of beauty and glory, beginning first with glory and beauty as found in the created order. Here the contention is that whereas notions of beauty spring ultimately from a Greek emphasis on proportion and balance, the Hebrew idea of glory is concerned with what overwhelms in its majesty and splendour, and is therefore more naturally equated with the eighteenth-century notion of sublimity. In addition, it is argued that, particularly in a modern context, it should not be presupposed that the arts are necessarily concerned with the creation of beauty. The second half of the article then turns to consider God in act and in internal life. With respect to the former, a critique is offered of the modern practice of describing the crucifixion as in itself beautiful. Finally, the author suggests that Balthasar's attempt to revive accounts of God as beautiful disguises major differences from the earlier tradition where simplicity rather than a rich complexity was taken as the defining criterion for such beauty.
Keywords: Art; Hans Urs Von Balthasar; Aesthetics; Beauty; Crucifixion; Glory; Music; Simplicity